Hotel investments in Singapore - Chan, Mei Wah (2009)
The launch of the Millennium - a new global hotel brand by the CDL Hotels Group on 18 October 1995 set a new era in the tourism industry in Singapore. The occasion witnessed a successful strategic decision by the Hong Leong parent company venturing into the hotel business in the 1970.